Immunogenicity of Golimumab and its Clinical Relevance in Patients With Ulcerative Colitis. Issue 9 (8th February 2019) - Adedokun, Omoniyi J; Gunn, George R; Leu, Jocelyn H; Gargano, Cynthia; Xu, Zhenhua; Sandborn, William J; Rutgeerts, Paul; Shankar, Gopi
Abstract: Background: Antidrug antibody (ADA) detection with standard bridging enzyme immunoassays (EIA) can yield false-negative results or underestimate titers through drug interference. A more sensitive assay was needed to determine clinical impact of antigolimumab antibodies. Methods: A high-sensitivity, drug-tolerant EIA (DT-EIA) was developed and cross-validated against the original EIA, and samples from induction/maintenance studies in golimumab-treated patients with ulcerative colitis were analyzed for ADAs using both methods. Immunogenicity results were compared, and pharmacokinetic, efficacy, and safety associations were evaluated. Results: An 8-fold increase in ADA-positive patients (21.8% DT-EIA vs 2.8% EIA) reflected DT-EIA improved sensitivity and drug tolerance. Most newly detected ADA-positive patients (using DT-EIA) had low antibody titers, whereas most with high antibody titers were ADA-positive with original EIA. With DT-EIA, week 44 median trough serum golimumab concentrations among ADA-positive patients were approximately half vs ADA-negative (0.51 vs 0.85 µg/mL [50 mg q4w]; 0.85 vs 1.60 µg/mL [100 mg q4w]). Antidrug antibody impact on golimumab concentrations was more notable at titers ≥1:100. During induction, ADAs had no notable impact on efficacy. During maintenance, proportions of patients maintaining clinical response through week 54 were lower using DT-EIA: 38.1% ADA-positive and 52.8% ADA-negative. Antidrug antibody status had no impact on injection-site reaction incidence. Conclusions: A more sensitive DT-EIA identified higher proportions of ADA-positive patients. A trend of decreasing drug concentrations with increasing ADA titers was observed. Pharmacokinetic impact was better elucidated with DT-EIA. Although development of ADA did not preclude efficacy, a trend toward decreased efficacy in ADA-positive vs ADA-negative patients was observed during maintenance treatment. Antidrug antibody status did not impact safety. Abstract : A new drug-tolerant EIA method was developed to enable detection of antibodies to golimumab in serum samples in the presence of golimumab. This method better elucidates the impact of immunogenicity and supports immunogenicity assessment in current and future golimumab studies.